2000
DOI: 10.1023/a:1006342300291
|View full text |Cite
|
Sign up to set email alerts
|

Eye problems in breast cancer patients treated with tamoxifen

Abstract: Our study suggests that five or more years of tamoxifen use increases risk of cataracts. Healthy women considering tamoxifen use to reduce risk of breast cancer should be advised of the possibility of cataract development. Women choosing such therapy should be diligent about receiving regular ocular exams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 6 publications
0
30
0
1
Order By: Relevance
“…17 Posterior subcapsular cataract can occur with busulphan, 5,[18][19][20] methotrexate, 5 toremifene and tamoxifen. [21][22][23] In a prospective study of breast cancer patients treated with tamoxifen and toremifene, annual cataract rates were found to be 6.8% and 6.2% respectively.…”
Section: Anterior Segment Side Effectsmentioning
confidence: 99%
“…17 Posterior subcapsular cataract can occur with busulphan, 5,[18][19][20] methotrexate, 5 toremifene and tamoxifen. [21][22][23] In a prospective study of breast cancer patients treated with tamoxifen and toremifene, annual cataract rates were found to be 6.8% and 6.2% respectively.…”
Section: Anterior Segment Side Effectsmentioning
confidence: 99%
“…Estrogens reduce low density lipoprotein (LDL) 1 cholesterol levels and elevate HDL cholesterol levels (2-4), although these beneficial lipid changes may not translate into favorable clinical results (5). Estrogens may also inhibit the development of colon cancer (5), inhibit the development of Alzheimer's disease (6), and inhibit development of cataracts (7,8). The multitude of estrogen responses matches the widespread distribution of estrogen receptors (ERs) throughout numerous organs, with ER␣ expression the highest in uterus, pituitary, kidney, and adrenal gland and ER␤ expression highest in ovary, uterus, bladder, and lung (9).…”
mentioning
confidence: 99%
“…7 Finally, a prospective chemopreventive trial 3 and a population case-control study found a higher incidence of cataracts, especially in standard or long-term users of chemotherapy. 48 This finding was recently challenged by a new case-control study, 49 although median tamoxifen exposure in this population was only 2.6 years.…”
Section: Discussionmentioning
confidence: 90%